Global, regional, and national burden of gastrointestinal cancers among adolescents and young adults from 1990 to 2019, and burden prediction to 2040 - Jieyu Peng; Shu Huang; Xiaohong Wang; Xiaomin Shi; Huan Xu; Ping Wang; Qi Chen; Wei Zhang; Lei Shi; Yan Peng; Nanjun Wang; Xiaowei Tang (BMC, 2024)
Abstract Background Gastrointestinal (GI) cancers have heavily burdened public health. Few studies reported GI cancer burden among adolescents and young adults (AYA). To address this gap, we explored the burden of GI cancer among people aged 15-39. Methods We retrieved data from the Global Burden of Disease Study 2019 Data Resources. The average annual percent change (AAPC) of rates was calculated by linear regression analysis of the natural logarithm. Bayesian age-period-cohort model was applied to predict the future burden. Results In 2019, there were 171,857 (95% uncertain interval [95% UI]: 157,092-187,974) new GI cancer cases with a rate of 5.79/100,000 (95% UI: 5.29-6.33) and 91,033 (95% UI: 83,156-99,399) deaths at a rate of 3.07/100,000 (95% UI: 2.80-3.35) among AYA. The number of prevalent cases and disability-adjusted life years (DALYs) were 722,573 (95% UI: 660,806-789,476) and 5,151,294 (95% UI: 4,706,065-56,188,77), with rates of 24.35/100,000 (95% UI: 22.27-26.60) and 173.57/100,000 (95% UI: 158.57-189.32) respectively. The overall rates of mortality (AAPC = -1.281, p < 0.001) and DALY (AAPC = -1.283, p < 0.001) of GI cancers declined during the past 30 years, while the incidence rate (AAPC = -0.270, p = 0.074) remained stable and the prevalence rate (AAPC = 1.066, p < 0.001) increased. The burden of colorectal cancer (CRC) and pancreatic cancer increased, while those of stomach cancer (SC) and liver cancer (LC) declined. Among the 21 GBD regions, East Asia exhibited the highest burden, while within the five SDI regions, high-middle SDI locations showed the highest rates across all four indicators. CRC, SC, and LC emerged as the primary culprits, attaining a position within the top ten absolute DALYs for all AYA cancers. There were predicted to be 315,792 new cases and 174,068 deaths of GI cancers among AYA in 2040. Conclusions Despite the decrease in mortality and DALY rates of GI cancers among AYA, they remain prevalent. The burden varied with locations, SDI levels, sexes, and cancer types. Sufficient attention and multi-party cooperation are needed to control the widespread public health issue.